Cell behaviour of Drosophila fat cadherin mutations in wing development. - Garoia, F.; Guerra, D.; Pezzoli, M.C.; Lopez-Varea, A.; Cavicchi, S.; Garcia-Bellido, A. (Mechanisms of Development, 2000)
We have studied several cell behaviour parameters of mutant alleles of fat (ft) in Drosophila imaginal wing disc development. Mutant imaginal discs continue growing in larvae delayed in pupariation and can reach sizes of several times those of wild-type. Their growth is, however, basically allometric. Homozygous ft cells grow faster than their twin cells in clones and generate larger territories, albeit delimited by normal clonal restrictions. Moreover, ft cells in clones tend to grow towards wing proximal regions. These behaviours can be related with failures in cell adhesiveness and cell recognition. Double mutant combinations with alleles of other genes, e.g. of the Epidermal growth factor receptor (DER) pathway, modify ft clonal phenotypes, indicating that adhesiveness is modulated by intercellular signalling. Mutant ft cells show, in addition, smaller cell sizes during proliferation and abnormal cuticular differentiation, which reflect cell membrane and cytoskeleton anomalies, which are not modulated by the DER pathway.